1992
DOI: 10.1007/bf01314627
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Interleukin-1?, Interleukin-2 and M-CSF-1 enhance the survival of newborn C57BL/6 mice inoculated intraperitoneally with a lethal dose of herpes simplex virus-1

Abstract: Recombinant Interleukin-1 alpha (IL-1 alpha), Interleukin-2 (IL-2) and recombinant macrophage colony-stimulating factor-1 (M-CSF-1) as well as combinations of IL-2 and M-CSF-1 were studied for their ability to protect seven-day-old C57BL/6 mice against HSV-1 infection. Treatment of the mice with IL-2, M-CSF-1 or combinations of IL-2 and M-CSF-1 significantly increased survival rates. Treatment with IL-1 alpha (10 U and 100 U/mouse) was most effective in protection against HSV-1, resulting in significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…HSV‐1 infection of gD3‐vaccinated mice resulted in a strong Th1 response, as indicated by the presence of IL‐2 and TNF‐α. 9 Similar to our results, it has been shown that, recombinant IL‐2 31 and TNF‐α32 can protect mice against lethal HSV‐1 infection and eye disease. We postulate that the reduced viral replication seen in the gD3 mice was because of a combination of this strong Th1 response (IL‐2 and TNF‐α) and high neutralizing antibody titres.…”
Section: Discussionsupporting
confidence: 88%
“…HSV‐1 infection of gD3‐vaccinated mice resulted in a strong Th1 response, as indicated by the presence of IL‐2 and TNF‐α. 9 Similar to our results, it has been shown that, recombinant IL‐2 31 and TNF‐α32 can protect mice against lethal HSV‐1 infection and eye disease. We postulate that the reduced viral replication seen in the gD3 mice was because of a combination of this strong Th1 response (IL‐2 and TNF‐α) and high neutralizing antibody titres.…”
Section: Discussionsupporting
confidence: 88%
“…The protective aspect of IL-2 may be in inducing the expansion of a CD4 ϩ T-helper cell population which interacts with B cells to produce specific antibodies. In addition, recombinant IL-2 appears capable of protecting mice against lethal HSV-1 infection (3). Thus, KOS vaccination may protect against corneal scarring by producing a rapid local IL-2 response following ocular challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason for lack of protection in newborn mice could be due to delayed antibody responses as well as defective macrophage and T cell function. (Berkowitz & Becker, 1992;Sarmiento, 1988). Even though all the above listed differences between newborn and adult mice logically appear to be possible reasons for the lack of protection in newborn mice, we do not have at this stage any experimental evidence to pinpoint the actual reason.…”
Section: Discussionmentioning
confidence: 99%